UN Special Rapporteur on Torture’s most recent report to the General Assembly: ‘Investigating, prosecuting and preventing wartime sexual torture, and providing rehabilitation to victims and survivors’ - Soley, Berta (Torture Journal, 2024)
The latest report by Dr. Alice Jill Edwards, UN Special Rapporteur on Torture (SRT), presented at the 79th session of the General Assembly on the 12th of June 2024.